RELIGIOUS TOLERANCE IN CONSTRUCTION ACTIVITIES DURING THE ERA OF AMIR TEMUR (The Journal of Interdisciplinary Human Studies, 2026)
This article highlights Amir Temur’s role not only as a military leader but also as a key figure in architectural and cultural development across Mawarannahr and Khorasan. He contributed immensely to the construction of cities, mosques, madrasas, mausoleums, palaces, gardens, and baths, with enduring examples in Samarkand, Shahrisabz, Bukhara, Tashkent, and Turkistan. Amir Temur personally oversaw building projects, restoration works, and urban planning, while attracting skilled craftsmen, architects, and artists. His monumental constructions, such as the Bibi-Khanym Mosque in Samarkand, illustrate his dedication to culture, science, and public welfare, and have been praised in historical sources including Dastur al-Muluk, Zafarnama, and the accounts of Ruy González de Clavijo.
Keywords: Amir Temur; Mawarannahr; Samarkand; Shahrisabz; Bukhara; Tashkent; Turkistan; Architecture